2023
DOI: 10.1186/s12909-023-04288-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and academic self-efficacy of nursing undergraduates under the normalization of COVID-19: multiple mediating roles of social support and mindfulness

Abstract: Background Nursing undergraduates’ academic self-efficacy is a significant factor in determining their learning motivation, cognition, and emotions. It has a significant impact on improving academic performance and achieving learning goals. Methods To explore the mechanism of psychological distress affecting the academic self-efficacy of nursing undergraduates, the generalized anxiety disorder scale-7, patient health questionnaire-9, academic self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Previous research has revealed a negative correlation between academic self-efficacy and stress [29]. On the one hand, when students confront pressure from various aspects such as academics and social interactions, their academic self-efficacy may be challenged [41]. Exposure to stress induces self-doubt and uncertainty regarding students' capabilities [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has revealed a negative correlation between academic self-efficacy and stress [29]. On the one hand, when students confront pressure from various aspects such as academics and social interactions, their academic self-efficacy may be challenged [41]. Exposure to stress induces self-doubt and uncertainty regarding students' capabilities [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence showed that most of previous studies on academic performance focused on students in colleges or universities, especially medical and nursing students (8)(9)(10)(11). However, few studies have been conducted on academic performance in middle and high school students.…”
Section: Introductionmentioning
confidence: 99%